"Fake News Is Anything They Say!" — Conceptualization and Weaponization of Fake News among the American Public. Issue 5 (2nd September 2020) - Tong, Chau; Gill, Hyungjin; Li, Jianing; Valenzuela, Sebastián; Rojas, Hernando
ABSTRACT: This study examines the articulation of public opinion about so-called fake news using a national survey ( N = 510) of U.S. adults conducted in 2018. We coded respondents' open-ended answers about what is "fake news" and found that while some respondents adopted a politically neutral, descriptive definition, others provided a partisan, accusatory answer. Specifically, the weaponization of fake news was evident in the way respondents used the term to blame adversarial political and media targets. Perceptions of fake news prevalence, partisanship strength, and political interest were associated with a higher likelihood of providing a politicized and accusatory response about fake news. Accusations were polarized as a function of partisan identity and positively correlated with affective polarization. Results are discussed in light of the linguistic distinction of the term and what it means in the context of news media distrust and polarization.